Identification of Hck Inhibitors As Hits for the Development of Antileukemia and Anti‐HIV Agents. Issue 8 (28th June 2013) - Tintori, Cristina; Laurenzana, Ilaria; La Rocca, Francesco; Falchi, Federico; Carraro, Fabio; Ruiz, Alba; Esté, José A.; Kissova, Miroslava; Crespan, Emmanuele; Maga, Giovanni; Biava, Mariangela; Brullo, Chiara; et al.
Abstract Hematopoietic cell kinase (Hck) is a member of the Src family of non‐receptor protein tyrosine kinases. High levels of Hck are associated with drug resistance in chronic myeloid leukemia. Furthermore, Hck activity has been connected with HIV‐1. Herein, structure‐based drug design efforts were aimed at identifying novel Hck inhibitors. First, an in‐house library of pyrazolo[3, 4‐d]pyrimidine derivatives, which were previously shown to be dual Abl and c‐Src inhibitors, was analyzed by docking studies within the ATP binding site of Hck to select the best candidates to be tested in a cell‐free assay. Next, the same computational protocol was applied to screen a database of commercially available compounds. As a result, most of the selected compounds were found active against Hck, with Ki values ranging from 0.14 to 18.4 μM, confirming the suitability of the computational approach adopted. Furthermore, selected compounds showed an interesting antiproliferative activity profile against the human leukemia cell line KU‐812, and one compound was found to block HIV‐1 replication at sub‐toxic concentrations.